2021
DOI: 10.1136/bmjopen-2021-052274
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum uric acid, all-cause mortality and cardiovascular mortality in peritoneal dialysis patients: systematic review and meta-analysis of cohort studies

Abstract: ObjectivesTo analyse the relationship between serum uric acid (SUA), all-cause and cardiovascular (CV) mortality in peritoneal dialysis (PD) patients to inform clinical practice and future research.DesignA systematic review of observational studies.Data sourcesPubMed, Embase, Web of Science, the Cochrane Library, China National Knowledge Infrastructure (CNKI), SinoMed, Chinese Science and Technology Journal Database (VIP) and Wan Fang databases were searched from their inception to January 2021 for cohort and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…In addition, Anderson [ 41 ] reported a systematic review and meta-analysis of death risk prediction for patients starting dialysis, unfortunately, the relationship between SUA and death was not explored. A recent meta-analysis by Xue et al [ 42 ] explored the relationship between SUA and all-cause and CVD mortality in PD patients and found that the results of prospective and retrospective cohort studies were inconsistent. However, they did not research the impact of intermediate levels of SUA on mortality compared with the highest and lowest levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Anderson [ 41 ] reported a systematic review and meta-analysis of death risk prediction for patients starting dialysis, unfortunately, the relationship between SUA and death was not explored. A recent meta-analysis by Xue et al [ 42 ] explored the relationship between SUA and all-cause and CVD mortality in PD patients and found that the results of prospective and retrospective cohort studies were inconsistent. However, they did not research the impact of intermediate levels of SUA on mortality compared with the highest and lowest levels.…”
Section: Discussionmentioning
confidence: 99%
“…The following data were extracted: the first author, year of publication, country, study design, patients, definition of spondylolisthesis, sample size, age, sex, BMI, disease duration, surgery types, follow-up time, number of reoperations, reasons for reoperation, reoperation methods, and risk factors of reoperation. The Newcastle–Ottawa Scale (NOS) was applied to evaluate the quality of cohort studies [ 15 ]. This scale consisted of three items: selection, comparability, and outcome.…”
Section: Methodsmentioning
confidence: 99%
“…This scale consisted of three items: selection, comparability, and outcome. This scale was scored a total of 9 points, and divided into low quality (0–3 points), fair quality (4–6 points), and high quality (7–9 points) [ 15 ].…”
Section: Methodsmentioning
confidence: 99%